Azimuthal anisotropy of charged particles with transverse momentum up to 100 GeV/c in PbPb collisions at sNN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier BV, 2018)
The Fourier coefficients v2 and v3 characterizing the anisotropy of the azimuthal distribution of charged particles produced in PbPb collisions at sNN=5.02 TeV are measured with data collected by the CMS experiment. The measurements cover a broad transverse momentum range, 1<pT<100 GeV/c. The analysis focuses on the pT>10 GeV/c range, where anisotropic azimuthal distributions should reflect the path-length dependence of parton energy loss in the created medium. Results are presented in several bins of PbPb collision centrality, spanning the 60% most central events. The v2 coefficient is measured with the scalar product and the multiparticle cumulant methods, which have different sensitivities to initial-state fluctuations. The values from both methods remain positive up to pT∼60–80 GeV/c, in all examined centrality classes. The v3 coefficient, only measured with the scalar product method, tends to zero for pT≳20 GeV/c. Comparisons between theoretical calculations and data provide new constraints on the path-length dependence of parton energy loss in heavy ion collisions and highlight the importance of the initial-state fluctuations.